Perlindungan Hukum Pemegang Saham Atas Ditolaknya Gugatan Perseroan Kepada Pengadilan Negeri - Ane Nor Cahya Ilmiah; Sumriyah Sumriyah (Hakim, 2024)
Guarantees of legal protection for each shareholder are regulated in the Limited Liability Company Law. The discussion in this journal is about providing protection to a shareholder who suffers a loss, legal remedies in a court institution, the basic rights of a shareholder, and filing a shareholder lawsuit due to losses arising from the company's GMS decision to the district court which is decided rejected. In this journal the author also emphasizes the importance of providing protection for shareholders and that very clear regulations regarding legal protection of shareholders are needed for its implementation in the Company Law in Indonesia. The results of the discussion in this research show that although there are arrangements or regulations governing Limited Liability Companies relating to providing protection to each shareholder, there is a lack of explanation regarding resistance to district court decisions that are felt to be detrimental to shareholders, where providing protection should first pay attention to the protection mechanism that will be given.